Small step in tech needed to upscale tropical island eradications - A. J. Burt; G. Harper; D. Ringler; M. Cagnato; L. A. Turnbull; J. C. Russell; A. Samaniego; T. Collier; S. Steibl; P. Carr; J. C. Daltry; A. Constance; et al. (Biological Invasions, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Transcriptomic Responses of Four Pelagophytes to Nutrient (N, P) and Light Stress - Yoonja Kang; Matthew J. Harke; Dianna L. Berry; Jackie L. Collier; Steven W. Wilhelm; Sonya T. Dyhrman; Christopher J. Gobler (Frontiers in Marine Science, 2021)
Pelagophytes are abundant picophytoplankton within open ocean ecosystems and the causative algae of harmful brown tide blooms in estuaries. The physiological capabilities facilitating the ecological success of pelagophytes in these diverse ecosystems remains poorly understood. Here, we investigated the transcriptional response of two coastal pelagophytes ( Aureococcus anophagefferens and Aureoumbra lagunensis ) and two open ocean pelagophytes ( Pelagococcus subviridis and Pelagomonas calceolata ) to conditions commonly found within the marine ecosystems where they thrive: low concentrations of nitrogen (N), phosphorus (P), or light. OrthoMCL was used to generate a total of 62,653 orthologous groups (OGs) with only a small fraction of these OGs (2,776 or 4.4%) being shared among all four pelagophytes. Of the commonly shared OGs, 8% were significantly differentially abundant under low N, P, or light with the majority associated with energy and lipid metabolism. Distinct responses among pelagophytes included increased abundance of transcripts encoding phosphate transporters ( Aureococcus ) and transcripts encoding a pyrophosphatase ( Aureococcus and Pelagomonas ) under low P, the expression of a suite of organic nitrogen-degrading enzymes under low N ( Aureoumbra and Pelagomonas ), increased abundance of transcripts encoding flavodoxins relative to ferredoxins ( Pelagomonas ) and transcripts encoding lysophospholipase ( Pelagococcus ) under low light, and both increases and decreases in abundance of transcripts encoding selenoproteins in all pelagophytes except Pelagococcus . Collectively, this study provides new information on the expressed gene compliment of these poorly characterized taxa and demonstrates that these pelagophytes possess a combination of shared and unique physiological features that likely facilitate their adaptation to distinct environmental conditions.

Cerebrospinal Fluid Ceruloplasmin, Haptoglobin, and Vascular Endothelial Growth Factor Are Associated with Neurocognitive Impairment in Adults with HIV Infection - A. R. Kallianpur; H. Gittleman; S. Letendre; R. Ellis; J. S. Barnholtz-Sloan; W. S. Bush; R. Heaton; D. C. Samuels; D. R. Franklin; D. Rosario-Cookson; D. B. Clifford; A. C. Collier; et al. (Molecular Neurobiology, 2019)

Neuroprotective activity of leukemia inhibitory factor is relayed through myeloid zinc finger-1 in a rat model of stroke - Stephanie M. Davis; Lisa A. Collier; Elspeth A. Foran; Christopher C. Leonardo; Craig T. Ajmo; Keith R. Pennypacker (Metabolic Brain Disease, 2019)

Traditional plant functional groups explain variation in economic but not size‐related traits across the tundra biome - H. J. D. Thomas; I. H. Myers‐Smith; A. D. Bjorkman; S. C. Elmendorf; D. Blok; J. H. C. Cornelissen; B. C. Forbes; R. D. Hollister; S. Normand; J. S. Prevéy; C. Rixen; G. Schaepman‐Strub; et al. (Global Ecology and Biogeography, 2019)
Aim Plant functional groups are widely used in community ecology and earth system modelling to describe trait variation within and across plant communities. However, this approach rests on the assumption that functional groups explain a large proportion of trait variation among species. We test whether four commonly used plant functional groups represent variation in six ecologically important plant traits. Location Tundra biome. Time period Data collected between 1964 and 2016. Major taxa studied 295 tundra vascular plant species. Methods We compiled a database of six plant traits (plant height, leaf area, specific leaf area, leaf dry matter content, leaf nitrogen, seed mass) for tundra species. We examined the variation in species‐level trait expression explained by four traditional functional groups (evergreen shrubs, deciduous shrubs, graminoids, forbs), and whether variation explained was dependent upon the traits included in analysis. We further compared the explanatory power and species composition of functional groups to alternative classifications generated using post hoc clustering of species‐level traits. Results Traditional functional groups explained significant differences in trait expression, particularly amongst traits associated with resource economics, which were consistent across sites and at the biome scale. However, functional groups explained 19% of overall trait variation and poorly represented differences in traits associated with plant size. Post hoc classification of species did not correspond well with traditional functional groups, and explained twice as much variation in species‐level trait expression. Main conclusions Traditional functional groups only coarsely represent variation in well‐measured traits within tundra plant communities, and better explain resource economic traits than size‐related traits. We recommend caution when using functional group approaches to predict tundra vegetation change, or ecosystem functions relating to plant size, such as albedo or carbon storage. We argue that alternative classifications or direct use of specific plant traits could provide new insights for ecological prediction and modelling.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Finding reference: a comparison of modelling approaches for predicting macroinvertebrate community index benchmarks - J. E. Clapcott; E. O. Goodwin; T. H. Snelder; K. J. Collier; M. W. Neale; S. Greenfield (New Zealand Journal of Marine and Freshwater Research, 2017)
Reference benchmarks are needed to assess the contemporary status of rivers and to establish restoration targets. We developed predictive models to estimate site‐specific reference values for a macroinvertebrate community index (MCI), which is used to indicate a range of human impacts on wadeable streams. We compared three statistical modelling approaches – general linear, boosted regression tree (BRT) and random forest (RF) – and tested the effect of spatial scale on predictive accuracy by developing national and regional BRT models. Using fitted flexible models (BRT, RF) and resetting predictors to reflect natural state provided the most accurate predictions of reference condition. Variation in reference MCI predictions from national and regional models was within the range observed from methodological and temporal variability. The proportion of native vegetation in upstream catchments was the primary predictor of MCI scores in all models, while secondary predictors varied regionally.

Leukemia Inhibitory Factor Protects Neurons from Ischemic Damage via Upregulation of Superoxide Dismutase 3 - Stephanie M. Davis; Lisa A. Collier; Christopher C. Leonardo; Hilary A. Seifert; Craig T. Ajmo; Keith R. Pennypacker (Molecular Neurobiology, 2017)

Following Natures Lead: On the Construction of Membrane-Inserted Toxins in Lipid Bilayer Nanodiscs - Narahari Akkaladevi; Srayanta Mukherjee; Hiroo Katayama; Blythe Janowiak; Deepa Patel; Edward P. Gogol; Bradley L. Pentelute; R. John Collier; Mark T. Fisher (The Journal of Membrane Biology, 2015)

Brain morphometric correlates of metabolic variables in HIV: the CHARTER study - S. L. Archibald; J. A. McCutchan; C. Sanders; T. Wolfson; T. L. Jernigan; R. J. Ellis; B. M. Ances; A. C. Collier; J. C. McArthur; S. Morgello; D. M. Simpson; C. Marra; et al. (Journal of NeuroVirology, 2014)

Sustainable roofing technology under multiple constraints: a decision-analytical approach - Z. A. Collier; D. Wang; J. T. Vogel; E. K. Tatham; I. Linkov (Environment Systems and Decisions, 2013)

Characterisation of amyloid-induced inflammatory responses in the rat retina - D. R. Howlett; S. T. Bate; S. Collier; A. Lawman; T. Chapman; T. Ashmeade; I. Marshall; P. J. B. Anderson; K. L. Philpott; J. C. Richardson; C. J. Hille (Experimental Brain Research, 2011)

The extent and significance of petroleum hydrocarbon contamination in Crater Lake, Oregon - Daniel R. Oros; Robert W. Collier; Bernd R. T. Simoneit (Hydrobiologia, 2007)

Clinical validation of the NeuroScreen - Ronald J Ellis; Scott R Evans; David B Clifford; Lauren R Moo; Justin C McArthur; Ann C Collier; Constance Benson; Ron Bosch; David Simpson; Constantin T Yiannoutsos; Yijun Yang; Kevin Robertson; et al. (Journal of NeuroVirology, 2005)

A modest glucokinase overexpression in the liver promotes fed expression levels of glycolytic and lipogenic enzyme genes in the fasted state without altering SREBP-1c expression - D.K. Scott; J.J. Collier; T.-T.T. Doan; A.S. Bunnell; M.C. Daniels; D.T. Eckert; R.M. O'Doherty (Molecular and Cellular Biochemistry, 2003)

Seasonal Changes in Reproductive Activity in the Potter's angelfish (Centropyge potteri) in Kaneohe Bay, Hawaii - Jason T. Collier; Toyoji Kaneko; Tetsuya Hirano; E. Gordon Grau (Environmental Biology of Fishes, 2003)

Stimulation of insulin-like growth factor-I production by recombinant bovine growth hormone in Mozambique tilapia, Oreochromis mossambicus - S. Kajimura; K. Uchida; T. Yada; L.G. Riley; J.C. Byatt; R.J. Collier; K. Aida; T. Hirano; E.G. Grau (Fish Physiology and Biochemistry, 2001)

Characterisation of lowland streams using a single‐station diurnal curve analysis model with continuous monitoring data for dissolved oxygen and temperature - Robert J. Wilcock; John W. Nagels; Graham B. McBride; Kevin J. Collier; Brent T. Wilson; Beat A. Huser (New Zealand Journal of Marine and Freshwater Research, 1998)
Twenty‐three lowland streams throughout the Waikato region, New Zealand, in catchments having a wide range of land uses and intensities, were monitored continuously over 3–4‐day periods for changes in dissolved oxygen (DO) and temperature. A single‐station diurnal curve model, DOFLO (Dissolved Oxygen at Low Flow), was used to produce reach‐averaged values for: K 2(20) , the reaeration coefficient at 20°C; P max. , the maximum daily rate of photosynthetic production of oxygen; R 20 , the daily respiration rate at 20°C; and Q 10 , the ratio of respiration rates 10°C apart. In addition, 24‐h average values for the ratio P/R were calculated and maximum and minimum values of DO and temperature tabulated for each site. Values of K 2(20) (0.05–40 d ‐1 , median 6.0 d ‐1 ) were in broad agreement with values calculated using a modified form of the O'Connor‐Dobbins equation. Values of gross primary production in daylight (0.5–29.2 g m ‐2 d ‐1 ) calculated from P max . (1.75–86.5 g m ‐3 d ‐1 ) were similar to data reported for other streams in agriculturally developed catchments in New Zealand and North America. Respiration rates (3.50–55.0 g m ‐3 d ‐1 ) were generally larger than values reported in the literature, and P/R ratios were mostly well below 1.0, indicative of heterotrophic respiration associated with decaying vegetation and other organic inputs and consistent with diurnal DO excursions of 40 to ≥120% saturation being commonly observed. Maximum daily temperatures up to 25.7°C (median 20.5°C) were weakly negatively correlated with DO minima. Five groupings of streams were identified from DOFLO parameter values, with K 2(20) being most critical in regulating average DO deficits.

Biochemical responses to sediment-associated contaminants in brown bullhead (Ameriurus nebulosus) from the Niagara River ecosystem - NANCY A. Eufemia; TRACY K. Collier; JOHN E. Stein; DAVID E. Watson; RICHARD T. Di Giulio (Ecotoxicology, 1997)

Accumulation and metabolism of carbon-14 labeled benzene, naphthalene, and anthracene by young coho salmon (Oncorhynchus kisutch) - William T. Roubal; Tracy K. Collier; Donald C. Malins (Archives of Environmental Contamination and Toxicology, 1977)

Bacterien-Haemagglutination - W. A. Collier; V. A. H. Tiggelman-Van Krugten; T. Tjong A. Hung (Antonie van Leeuwenhoek, 1955)